Basis of Globally Admissible Rules for Logic S4 - V.V. Rimatskiy (Известия Иркутского государственного университета: Серия "Математика", 2024)
Setting the basic rules of inference is fundamental to logic. The most general variant of possible inference rules are admissible inference rules:in logic $L$, a rule of inference is admissible if the set of theorems $L$ is closed with respect to this rule.